Fabrication of Surface Plasmon Resonance Sensor Surface with Control of the Non-Specific Adsorption and Affinity for the Detection of 2,4,6-Trinitrotoluene Using an Antifouling Copolymer - Yatabe, Rui; Onodera, Takeshi; Toko, Kiyoshi (Frontiers in Bioengineering and Biotechnology, 2014)
We fabricated a surface plasmon resonance (SPR) sensor using a hydrophilic polymer for the highly sensitive detection of 2,4,6-trinitrotoluene (TNT). The hydrophilic polymer was made from mono-2-(methacryloyloxy)ethylsuccinate (MES) and 2-hydroxyethylmethacrylate (HEMA) by surface-initiated atom transfer radical polymerization (SI-ATRP). The detection of TNT was carried out by displacement assay with the SPR measurement. In displacement assay, the affinity between anti-TNT antibody and the sensor surface, affects to the sensitivity. In the SPR measurement, nonspecific adsorption should be controlled because SPR sensor cannot discriminate between specific and nonspecific adsorption. Therefore, the affinity and nonspecific adsorption were controlled by changing the ratio of HEMA to MES. A detection limit of 0.4 ng/ml (ppb) for TNT was achieved using a sensor surface with the lowest affinity without nonspecific adsorption.